ANALISIS KINERJA FKTP PEMERINTAH DI ERA JKN DENGAN METODE BALANCED SCORECARD: STUDI KASUS DI PUSKESMAS BANDAR BARU TAHUN 2022 - Hasnur, Hanifah (UI Scholars Hub, 2023)
The health efforts at health facilities have entered a new phase in the current era of Indonesian National Health Insurance (NHI). The Bandar Baru Health Center (Puskesmas), one of the largest Puskesmas in Pidie Regency with the most significant income from the NHI, is required to have quality health services, which at the same time also needs to be efficient in using its resources. This study uses the Balanced Scorecard method to determine the performance of the government's FKTP, in this case, the Bandar Baru Health Center, in the current NHI era. This quantitative descriptive research collects primary and secondary data to analyze the financial, customer, internal business, and development perspectives. The results of the study show that the Bandar Baru Health Center, from a financial perspective, is still lacking in growth due to the expansion of the sub-health center below it, however; the Puskesmas has made savings, which can be seen from the Balanced Economic Level Value is economical (Tec < 100%; 2019-2020) and less economical in 2021 (Tec=100%), the value of the Effectiveness Level is not effective (Tev < 100%; 2019-2021), and the value of the Efficient level is not efficient (Tef =100%; 2019-2020) and efficient in 2021 (Tef < 100%). From the customer's perspective, the lowest satisfaction index is on the facilities and infrastructure of the Bandar Baru Puskesmas. Meanwhile, from an internal business perspective, employee turnover is low even though employee training still needs to be improved. Efforts are needed to increase innovative health programs that can improve the performance of the Puskesmas and increase the number of patients registered to increase the financial growth of the Bandar Baru Health Center.